2021
DOI: 10.3389/fncel.2021.743532
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of CD146 in Schwann Cells Following Peripheral Nerve Injury Modulates Schwann Cell Function in Regeneration

Abstract: CD146 is cell adhesion molecule and is implicated in a variety of physiological and pathological processes. However, the involvement of CD146 in peripheral nerve regeneration has not been studied yet. Here, we examine the spatial and temporal expression pattern of CD146 in injured mouse sciatic nerve via high-throughput data analysis, RT-PCR and immunostaining. By microarray data analysis and RT-PCR validation, we show that CD146 mRNA is significantly up-regulated in the nerve bridge and in the distal nerve st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…MCAM, also known as CD146, is a membrane CAM of the immunoglobulin superfamily and functions in mammalian nervous system development 32 . MCAM also facilitates nerve regeneration and regulates cell migration and proliferation, suggesting a role for a fibroblast-neuronal axis contributing to PNS hypertrophy and activation in PN 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…MCAM, also known as CD146, is a membrane CAM of the immunoglobulin superfamily and functions in mammalian nervous system development 32 . MCAM also facilitates nerve regeneration and regulates cell migration and proliferation, suggesting a role for a fibroblast-neuronal axis contributing to PNS hypertrophy and activation in PN 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…MCAM, also known as CD146, is a membrane CAM of the immunoglobulin superfamily and functions in mammalian nervous system development 33 . MCAM also facilitates nerve regeneration and regulates cell migration and proliferation, suggesting a role for a fibroblast-neuronal axis contributing to PNS hypertrophy and activation in PN 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the CD146 molecule may have an impact on peripheral nerve regeneration. Shen et al [ 136 ] suggested that CD146 not only had a key role in promoting of blood vessel regeneration but also regulated cell migration. Functional assessments showed that knockdown of CD146 decreased proliferation and viability of Schwann cells but increased their migration.…”
Section: Markers For Specialized Populations Within Mscsmentioning
confidence: 99%
“…Functional assessments showed that knockdown of CD146 decreased proliferation and viability of Schwann cells but increased their migration. Additionally, CD146 was upregulated in Schwann cells and cells associated with blood vessels following mouse peripheral nerve injury [ 136 ]. Taking together described CD146+ cells properties and its key role in vascular endothelial cell activity and angiogenesis, this subpopulation could be used in vascular smooth muscle, endothelial, or IVDs regeneration.…”
Section: Markers For Specialized Populations Within Mscsmentioning
confidence: 99%